1976
DOI: 10.1159/000180745
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Metabolism in Renal Diseases

Abstract: Fluorescence microscopy in experimental hexachlorobenzene porphyria in rats has demonstrated porphyrin deposits in the epithelial cells of the proximal renal tubules and the loop of Henle. In the glomeruli, interstitium, distal tubules, and the collecting tubules, no porphyrins were detected. The similarity of this finding with the data on some forms of porphyrinuria and porphyria in man suggests that the proximal tubules and the loop of Henle play an important role in the mechanism of renal porphyrin excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The work of Ivanov et at. [10] on experimental porphyria in rats supports ear lier observations [3,19] that the proximal tubules and loop of Henle play a major role in urinary porphyrin excretion. Clinical interest in the porphyrin status in chronic renal failure has been aroused by the dermatologic abnormali ties, especially cutaneous blistering eruptions, reported recently [8,12.17].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The work of Ivanov et at. [10] on experimental porphyria in rats supports ear lier observations [3,19] that the proximal tubules and loop of Henle play a major role in urinary porphyrin excretion. Clinical interest in the porphyrin status in chronic renal failure has been aroused by the dermatologic abnormali ties, especially cutaneous blistering eruptions, reported recently [8,12.17].…”
Section: Introductionsupporting
confidence: 69%
“…No increase was ob served in the plasma COPRO, nor of the liver porphyrins, yet marked porphyrin increases were observed in their kidneys specifically located in the loop of Henle and proxi mal tubules. Other workers have reported similar results [10] but assumed the porphyrins had accumulated in the kidney.…”
Section: Discussionmentioning
confidence: 53%
“…There have been several observations of excess por phyrins in renal tissues, and in the more detailed, involving both humans [5] and animals [6,7] with disturbed heme metabolism, the greatest concentrations were found in the proximal convoluted tubules. Few researchers, however, have investigated renal porphyrin synthesis per se, since it is generally assumed that any excesses in the kidney result from the passive deposition of elevated porphyrins from the filtrate.…”
mentioning
confidence: 99%
“…with much lower levels of uroporphyrin (URO), sometimes occurring. These COPRO levels have been shown to decrease [12] and dis appear [4] in subjects with chronic renal failure, whilst an earlier study [10] revealed normal urinary COPRO levels in 7 azotemic patients after receiving transplanted kidneys which exhibited good renal function. These findings indi cate that urinary COPRO levels may be related to renal function.…”
Section: Introductionmentioning
confidence: 88%